2023
DOI: 10.1021/acsami.2c22931
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Inspired FeMo2S4 Microspheres as Bifunctional Electrocatalysts for Boosting Hydrogen Oxidation/Evolution Reactions in Alkaline Solution

Abstract: Developing robust and effectual nonprecious electrocatalysts for the bifunctional hydrogen oxidation and evolution reactions (HOR and HER) in alkaline electrolyte is of critical significance for the realization of future hydrogen economy but challenging. Herein, this work demonstrates a new routine for the preparation of bio-inspired FeMo2S4 microspheres via the one-step sulfuration of Keplerate-type polyoxometalate {Mo72Fe30}. The bio-inspired FeMo2S4 microspheres feature potential-abundant structural defects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…[35] A presentative example of supramolecular aggregate by Hbonding self-assembly is melamine cyanurate (MCA), which is built by melamine (MEL) and cyanuric acid. [36] Araby and coworkers [37] reported that the addition of 5.0 wt% MCA can increase the tensile strength and toughness of thermoplastic polyurethane (TPU) by 8.3% and 2.7%, respectively, owing to the formation of H-bonds between TPU chains and MCA. Furthermore, MCA is also known as a recyclable and environmentally friendly fire retardant due to the high contents of N element within its structure.…”
Section: Supramolecular Fire-retardant Aggregates Based On Hydrogen B...mentioning
confidence: 99%
See 1 more Smart Citation
“…[35] A presentative example of supramolecular aggregate by Hbonding self-assembly is melamine cyanurate (MCA), which is built by melamine (MEL) and cyanuric acid. [36] Araby and coworkers [37] reported that the addition of 5.0 wt% MCA can increase the tensile strength and toughness of thermoplastic polyurethane (TPU) by 8.3% and 2.7%, respectively, owing to the formation of H-bonds between TPU chains and MCA. Furthermore, MCA is also known as a recyclable and environmentally friendly fire retardant due to the high contents of N element within its structure.…”
Section: Supramolecular Fire-retardant Aggregates Based On Hydrogen B...mentioning
confidence: 99%
“…To counter this challenge, MCA is usually employed to combine with other materials to construct more efficient fire retardant via H-bonding interactions. [39] Araby and coworkers [37] developed MCA@α-ZrP as a novel hybrid fire retardant for TPU. The addition of 5.0 wt% MCA@α-ZrP reduces the peak heat release rate (PHRR) and total heat release (THR) of TPU by 49.7%, and 12.6%, respectively.…”
Section: Supramolecular Fire-retardant Aggregates Based On Hydrogen B...mentioning
confidence: 99%
“…22–24 Recently, various well-defined composites of POMs have been reported as efficient electrocatalysts 25–28 as well as precursors for the hydrogen evolution reaction (HER). 29–32 The studies revealed that the presence of POMs assisted in inducing activity in an otherwise inactive counterpart via a synergistic effect. POMs incorporated into a 2D-carbon matrix also exhibited enhanced activity in energy applications as compared to the parent materials.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to acidic electrolysis, liquid alkaline electrolysis is a more well-developed technology. Alkaline electrolysis is less costly as it employs non-noble-metal electrocatalysts such as Ni, Co, Fe, Mn, and Mo. Additionally, compared to that in the alkaline medium, significant corrosion can be observed in an acidic medium.…”
Section: Introductionmentioning
confidence: 99%